Functional connectivity in the developing language network in 4‐year‐old children predicts future reading ability. Issue 2 (28th October 2020) - Jasińska, Kaja K.; Shuai, Lan; Lau, Airey N. L.; Frost, Stephen; Landi, Nicole; Pugh, Kenneth R.
Abstract: Understanding how pre‐literate children's language abilities and neural function relate to future reading ability is important for identifying children who may be at‐risk for reading problems. Pre‐literate children are already proficient users of spoken language and their developing brain networks for language become highly overlapping with brain networks that emerge during literacy acquisition. In the present longitudinal study, we examined language abilities, and neural activation and connectivity within the language network in pre‐literate children (mean age = 4.2 years). We tested how language abilities, brain activation, and connectivity predict children's reading abilities 1 year later (mean age = 5.2 years). At Time 1, children (n = 37) participated in a functional near infrared spectroscopy (fNIRS) experiment of speech processing (listening to words and pseudowords) and completed a standardized battery of language and cognitive assessments. At Time 2, children (n = 28) completed standardized reading assessments. Using psychophysiological interaction (PPI) analyses, we observed significant connectivity between the left IFG and right STG in pre‐literate children, which was modulated by task (i.e., listening to words). Neural activation in left IFG and STG and increased task‐modulated connectivity between the left IFG and right STG was predictive of multiple reading outcomes. Increased connectivity was associated later with increased reading ability. Abstract : Functional connectivity for language in 4‐year‐old pre‐literate children predicts future reading. Neural activation and task‐dependent connectivity (PPI) between LIFG and RSTG was predictive of multiple reading outcomes one year later.